DETERMINAN MINAT BERWIRAUSAHA GEN Z PROVINSI RIAU: Pengaruh Literasi Digital, Self Efficacy dan Risk Tolerance - Dichi Selma Yuni; Aminah Nuriyah (IAIN BONE, 2025)
This study aims to determine and analyze the influence of digital literacy on the entrepreneurial interest of Gen Z in Riau Province, the influence of self efficacy on the entrepreneur6ial interest of Gen Z in Riau Province, and the influence of risk tolerance on the entrepreneurial interest of Gen Z in Riau Province. The method used in this study is a quantitative method. The population in this study were all Gen Z (aged 15-27 years) from Riau Province. The sampling technique in this study was using a purposive sampling technique with a total of 190 respondents. The data collection technique was by distributing a Google Form questionnaire to Gen Z in Riau Province. This study uses descriptive statistical data analysis techniques, statistical analysis in this study was using SMARTPLS 4 software to process data and data analysis methods using Partial Least Square Structural Equation Modelling (PLS-SEM). The result of this study indicate that partially the variables of digital literacy, self efficacy and risk tolerance have a positive and significant effect on the entrepreneurial interest of Gen Z in Riau Province.